NSC KIPT participation in the CMS (CERN) collaboration - Levchuk, L.G.; Marekhin, S.V.; Nemashkalo, A.A.; Popov, V.P.; Sorokin, P.V.; Zatserklianiy, A.E. (Вопросы атомной науки и техники, 2001)
In conformity with the Agreement of 03.04.1993 between the Government of Ukraine and CERN, the National Science Center Kharkov Institute of Physics & Technology (NSC KIPT) takes part in the international CMS program. Its collaboration duties include: the manufacture of scintillation elements for the forward hadron calorimeter and investigation of their characteristics; the simulation of physical processes in the CMS detector; the preparation for processing experimental results.